2021
DOI: 10.3389/fpubh.2021.685860
|View full text |Cite
|
Sign up to set email alerts
|

Non-pharmacological Approaches to Depressed Elderly With No or Mild Cognitive Impairment in Long-Term Care Facilities. A Systematic Review of the Literature

Abstract: Introduction: Compared to old people who live at home, depressive symptoms are more prevalent in those who live in long-term care facilities (LTCFs). Different kinds of non-pharmacological treatment approaches in LTCFs have been studied, including behavioral and cognitive-behavioral therapy, cognitive bibliotherapy, problem-solving therapy, brief psychodynamic therapy and life review/reminiscence. The aim of the current review was to systematically review non-pharmacological treatments used to treat depressed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
16
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 74 publications
(123 reference statements)
1
16
0
1
Order By: Relevance
“…To meet the needs of participants with different function status, the mode of horticulture activities can be adjusted to suit their capabilities. Though the optimal protocol is still unknown, it has been reported that the overall duration of the intervention delivered seemed to have a greater impact on treatment effectiveness than the duration of each single session [37]. Based on the results of the RCT conducted in the LTCFs, activity programs with the intervention duration up to eight weeks have been proven to be effective in improving the mental health outcomes [22,29].…”
Section: Discussionmentioning
confidence: 99%
“…To meet the needs of participants with different function status, the mode of horticulture activities can be adjusted to suit their capabilities. Though the optimal protocol is still unknown, it has been reported that the overall duration of the intervention delivered seemed to have a greater impact on treatment effectiveness than the duration of each single session [37]. Based on the results of the RCT conducted in the LTCFs, activity programs with the intervention duration up to eight weeks have been proven to be effective in improving the mental health outcomes [22,29].…”
Section: Discussionmentioning
confidence: 99%
“…In particular, physical aging and its consequences are harmful to psychological health and cause the onset of negative emotional states and disabling problems, thus posing a threat to older people's autonomy in everyday life and mental health. Due to these emergencies and to the lack of effective treatments for neurodegenerative diseases, the scientific community has been stimulated to explore the validity of a wide range of rehabilitative and psychosocial interventions defined as nonpharmacological treatments [2]. In addition, while brain reorganization capacity was previously thought to be limited to early childhood, the discovery that neuroplasticity continues with age has led to the development of tools and techniques to promote it even during aging in order to cope with functional and cognitive decline and strengthen already existing skills [3].…”
Section: Introductionmentioning
confidence: 99%
“…Typical nonpharmacological treatments include psychotherapy and physical exercise. While these treatments do not have drug-related side effects, they act slowly and can be easily influenced by patients’ subjective feelings . Pharmacological treatments mainly consist of antidepressants and other drugs with antidepressant effects.…”
Section: Introductionmentioning
confidence: 99%